Development of Presentation Tourist Information to Promote Quality Tourism of Pattaya City - Rooymai, Noodruedee (International Journal of Multidisciplinary in Management and Tourism, 2021)
This study aims (1) to find a source of information that influences foreign tourists visiting Pattaya, (2) to examine the impact of news on the behavior of foreign tourists visiting Pattaya, and (3) as implications for policymakers and destination businesses. The sample was 400 inbound tourists to answer questionnaires based on convenience sampling. Descriptive and content analyses are the main analysis methods. The result offers policymakers to design and improve advertising and public relations and create a positive Pattaya image for foreign tourists. This study finds that most tourists are aware of the negative information of Pattaya City at a moderate level. Negative information with the highest mean is plunder news and city of sex show news. Most foreigners trust the negative information of Pattaya City at a moderate level. Negative information with the highest mean is city of sex show news, motorcycle accident news, and car accident news. Most foreigners are afraid of the negative information of Pattaya City at a moderate level.